MO253A RANDOMIZED, DOUBLE-BLIND, PLACEBO-CONTROLLED DOSE-RANGING STUDY (LUMINA-1 STUDY) TO EVALUATE THE SAFETY AND EFFICACY OF CCX140 IN SUBJECTS WITH FOCAL SEGMENTAL GLOMERULOSCLEROISS (FSGS)*. (29th May 2021) - Cortazar, Frank; Niles, John L; Schall, Thomas J; Staehr, Peter
Abstract: Background and Aims: Primary Focal Segmental Glomerulosclerosis (FSGS) is the most common primary glomerular disease in patients with end stage renal disease in the United States. Current treatment regimens target reduction in proteinuria, but may have limited response or exhibit disease recurrence. CCX140 is an orally-administered selective small molecule inhibitor of the C-C chemokine receptor 2 (CCR2) under investigation for the treatment reduction of proteinuria in patients with FSGS. The primary objectives of this study were to evaluate the safety and efficacy of CCX140 in patients with FSGS and a urine protein to creatinine ratio (UPCR) of ≥1 g/g. Efficacy was assessed by the change in UPCR. Method: Forty-six adult patients with primary or genetic FSGS were randomized into a double-blind, placebo-controlled Phase 2 dose-ranging study designed to evaluate the safety and efficacy of CCX140. Changes of urinary protein excretion estimation (UPCR) from baseline to Week 12 were measured in four blinded treatment groups (three active CCX140 doses of 5 mg once daily, 10 mg and 15 mg twice-daily (BID) vs placebo). Starting at Week 12, all subjects including those in the placebo group received the CCX140, 15 mg BID for an additional 12 weeks, and UPCR changes from Week 12 to Week 24 were assessed. There was a 4-week follow-up period from Week 24 to Week 28 where no CCX140 was administered. Results: In the intent to treat (ITT) analysis of UPCR changes at Week 12 relative to baseline, the 15 mg BID CCX140 group exhibited the greatest reduction of UPCR (median reduction from baseline 0.9 g/g or approximately 30%, and approximately 25% reduction from baseline for the geometric mean), but that did not differ significantly from the placebo group (median reduction from baseline 0.45 g/g; or approximately 22%, and approximately 23% reduction from baseline for the geometric mean). Also, after crossover of the blinded portion of the trial to 15 mg BID active dosing, the previous placebo group did not appear to exhibit an additional reduction of UPCR. CCX140 at all doses was well-tolerated, with no serious adverse events (SAEs) during the blinded trial and a numerically lower rate of treatment-emergent adverse events in the CCX140 treatment groups. Conclusion: In the study, CCX140 did not demonstrate a therapeutically meaningful reduction in proteinuria relative to the control group after 12 weeks of blinded treatment. The study provides insights into the natural disease progression of patients with primary or genetic FSGS as part of a clinical trial setting.